Performance of a cost‐effective and automated blood counting system for resource‐limited settings operated by trained and untrained users. Issue 2 (7th August 2017) - Xie, Dengling; Xie, Yanjun; Liu, Peng; Tong, Lieshu; Hu, Chuanzhen; Shao, Pengfei; Chu, Kaiqin; Smith, Zachary J.
Abstract : Current flow‐based blood counting devices require expensive and centralized medical infrastructure and are not appropriate for field use. In this article we report a streamlined, easy‐to‐use method to count red blood cells (RBC), white blood cells (WBC), platelets (PLT) and 3‐part WBC differential through a cost‐effective and automated image‐based blood counting system. The approach consists of using a compact, custom‐built microscope with large field‐of‐view to record bright‐field and fluorescence images of samples that are diluted with a single, stable reagent mixture and counted using automatic algorithms. Sample collection utilizes volume‐controlled capillary tubes, which are then dropped into a premixed, shelf‐stable solution to stain and dilute in a single step. Sample measurement and analysis are fully automated, requiring no input from the user. Cost of the system is minimized through the use of custom‐designed motorized components. We compare the performance of our system, as operated by trained and untrained users, to the clinical gold standard on 120 adult blood samples, demonstrating agreement within Clinical Laboratory Improvement Amendments guidelines, with no statistical difference in performance among different operator groups. The system's cost‐effectiveness, automation and performance indicate that it can be successfully translated for use in low‐resource settings where central hematology laboratories are not accessible. Abstract : We report an easy‐to‐use method to count red blood cells, white blood cells, platelets and 3‐part WBC differential through a cost‐effective and automated image‐based microscopy system. The performance of our system agrees with clinical standards to within Clinical Laboratory Improvement Amendments guidelines, with no statistical difference in performance among trained and untrained users. The system's cost and performance indicate that it can be successfully translated to low‐resource settings where central laboratories are not accessible.